Analisis Proses Assy Engine Mounting / Swing Arm Motor Beat 110CC - Luqman Dwi Septian; Oleh Oleh (Peneliti.net, 2022)
The development of science and technology is experiencing very rapid growth, including in the automotive industry. This study discusses the analysis of the Honda Beat 110cc swing arm shaft based on data in the field. The swing arm axis analysis is to maximize the maximum value that must be taken. The wheel axle is one of the components that function to support the body and the load of the vehicle. The purpose of this research analysis is to determine the amount of load received on the swing arm shaft Honda Beat 110cc. The research method used is through direct observation of literature studies that have been obtained in the form of books or journals and the internet as references. This calculation is carried out to be used as a benchmark as a comparison material from the calculation results with wheel axle information data in the field. This comparison material is based on several basic theories and conclusions obtained from the calculation results. With the conclusion that the material used to design the swing arm swing shaft with flexibility is 11.20 mm with a good safety factor so that it is safe to use the design results show the value for the same diameter with an amazing size